ADMINISTRASI KELEMBAGAAN PENDIDIKAN ISLAM DALAM MENGELOLA KRISIS MORAL PESERTA DIDIK PADA ERA KECERDASAN BUATAN - Resti Elisa Puteri (CV JK Riset Publishing Group, 2026)
This research is motivated by the increasing moral crisis among students triggered by advances in artificial intelligence (AI) in Islamic educational institutions. The research aims to analyze the role of Islamic educational institutional administration in managing the student moral crisis in the AI era. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation in three public madrasah aliyah. The findings indicate that effective institutional administration through Islamic value-based curriculum planning, strengthening student governance, empowering teachers as moral agents, and wise technology integration can mitigate the negative impacts of AI. The research concludes that Islamic educational institutions need to adaptively transform their administrative models to maintain students' moral integrity amid massive digitalization